Comparison of Frequency of Success in Identification of Etradural Space by LOR Technique with air and Saline During Etradural Anaesthesia in Lower Segment Caesarean Section (Journal of Fatima Jinnah Medical University, 2018)
This study was conducted to compare the frequency of success in identifying etradural space by LOR technique (LOR) with air or saline during etradural anaesthesia in lower segment caesarean section. Method: In this experimental study, 70 patients of ASA I and II of age 18-40 years, undergoing caesarean section were selected and divided in 2 groups, In Group A, 3ml of Air & in Group B 3ml of Saline was used respectively for the localization of etradural space by LOR technique method. Conclusion: It was concluded that for the identification of etradural space, Saline has the minimum unblocked segments and complications as compared to Air.
Keywords: Etradural Anaesthesia, Caesarean Section. Resistance,